Understanding How People with Limited Mobility Use Multi-Modal Input - Wentzel, Johann David; Junuzovic, Sasa; Devine, James; Porter, John; Mott, Martez (ACM CHI Conference on Human Factors in Computing Systems (CHI2022), 2022)
People with limited mobility often use multiple devices when interacting with computing systems, but little is known about the impact these multi-modal configurations have on daily computing use. A deeper understanding of the practices, preferences, obstacles, and workarounds associated with accessible multi-modal input can uncover opportunities to create more accessible computer applications and hardware. We explored how people with limited mobility use multi-modality through a three-part investigation grounded in the context of video games. First, we surveyed 43 people to learn about their preferred devices and configurations. Next, we conducted semi-structured interviews with 14 participants to understand their experiences and challenges with using, configuring, and discovering input setups. Lastly, we performed a systematic review of 74 YouTube videos to illustrate and categorize input setups and adaptations in-situ. We conclude with a discussion on how our findings can inform future accessibility research for current and emerging computing technologies. ACM CHI 2022 Presentation